KESESUAIAN PEMBELAJARAN KETERAMPILAN MENYIMAK PADA MATERI DW VIDEO NICOS WEG A1 UNTUK SISWA KELAS XI SEMESTER I - Paramesthi, Elvaretta Paramesthi; Samsul, Suwarno Imam (LATERNE, 2021)
Listening comprehension skill is the first language learning skill that someone gets by doing communication activity (Gereda, 2020:28). So that there is no misunderstanding between the listener and speaker, exercising listening comprehension skill consistently and periodically is needed. That is considered very necessary because the level of listening abiity of Indonesian students is still 58%, Ayu (in Qudus & Yusri, 2017:128). Technology advances offer the teachers an innovative and a creative solution by choosing other teaching materials sources and learning media to support teaching and learning activities in school, one of the learning medias at learngerman.dw.com Nicos Weg A1 Wohnen can be used as an option. Wohnen theme is mentioned on the curriculum as Wohnung, those same themes will be analyzed through literature study to find out whether the learning video is appropriate with the german curriculum materials for eleventh grade first semester. The data sources in this study are 4 learning videos Nicos Weg A1 with the theme Wohnen and the data of this study is the curriculum 2013 which is found in Themen neu Arbeitsbuch (German Textbook) Chapter 5. According to the result of data analysis of this research concludes that the video Nicos Weg A1 Wohnen is not appropriate enough with the materials of curriculum, because of less extensive discussion of the material on the videos so it causes the whole materials listed on the curriculum not to be fulfilled. That is the reason why the teacher should search for supporting teaching materials to fulfil the material needs of the curriculum 2013. This research has found 82 discrepancies of Wortschatz, which includes verbs, adjectives and nouns, in the other hand there is 11 discrepancies of Redemittel. On the aspect of suitability has been found 43 suitabilities of Wortschatz and 6 for Redemittel. Apart from suitability and discrepancy, there are also additional vocabularies and utterances on Nicos Weg video, which are not found on curriculum 2013, namely 22 Redemittel and 42 Wortschatz